2016
DOI: 10.3389/feart.2016.00044
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the AR4 CMIP3 and the AR5 CMIP5 Model and Projections for Precipitation in Northeast Brazil

Abstract: This article compares the sensitivity of IPCC CMIP3-AR4 and CMIP5-AR5 models used on the latest reports from the Intergovernmental Panel on Climate Change (IPCC) in representing the annual average variations (austral summer and autumn) on three regions in Northeastern Brazil (NNEB) for the periods 1979-2000 using the CMAP (Climatology Merged Analysis of Precipitation) data as reference. The three areas of NNEB chosen for this analysis were the semiarid, eastern, and southern regions. The EOF analysis was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
7
0
2
Order By: Relevance
“…CCSM4 model shows higher maximum values than GPCP (Figure 1b), and the CAN model has the lowest values over Brazil among models results (Figure 1e). These results are consistent with previous works using several coupled models (e.g., Li et al ., 2006; Vera et al ., 2006; Bombardi and Carvalho, 2009; Jones and Carvalho, 2013; Gulizia and Camilloni, 2015; Sierra et al ., 2015; Alves et al ., 2016; Díaz and Vera, 2017). Jones and Carvalho (2013) results suggest problems with CMIP5 models to simulate the maximum precipitation over the core of the monsoon.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…CCSM4 model shows higher maximum values than GPCP (Figure 1b), and the CAN model has the lowest values over Brazil among models results (Figure 1e). These results are consistent with previous works using several coupled models (e.g., Li et al ., 2006; Vera et al ., 2006; Bombardi and Carvalho, 2009; Jones and Carvalho, 2013; Gulizia and Camilloni, 2015; Sierra et al ., 2015; Alves et al ., 2016; Díaz and Vera, 2017). Jones and Carvalho (2013) results suggest problems with CMIP5 models to simulate the maximum precipitation over the core of the monsoon.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Alves et al . (2016) compared the CMIP3 and CMIP5 models for Northeastern Brazil and found similar errors in both phase models. Sierra et al .…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Although interest in climate change studies has increased, there have been fewer studies investigating climate extreme events. Most studies have examined the variation of monthly, annual, and seasonal mean values of climate parameters (Almazroui, Nazrul Islam, Saeed, Alkhalaf, & Dambul, 2017; Alves et al, 2016; Gagnon, Singh, Rousselle, & Roy, 2005; Ludwing et al, 2019; Marengo et al, 2009; Palatella, Miglietta, Paradisi, & Lionello, 2010; Pandey, Das, Jhajharia, & Pandey, 2018; Pervez & Henebry, 2014; Silva & Mendes, 2015). To facilitate research on climate extremes and their trends, the Expert Team on Climate Change Detection and Indices (ETCCDI) of WMO and the World Climate Research Program (WCRP) have identified a set of 27 indicators describing the extreme character of climate events.…”
Section: Introductionmentioning
confidence: 99%